2013
DOI: 10.1063/1.4796197
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a FAST semi-submersible floating wind turbine numerical model with DeepCwind test data

Abstract: There are global efforts in the offshore wind community to develop reliable floating wind turbine technologies that are capable of exploiting the abundant deepwater wind resource. These efforts require validated numerical simulation tools to predict the coupled aero-hydro-servo-elastic behavior of such systems. To date, little has been done in the public domain to validate floating wind turbine simulation tools. This work begins to address this problem by presenting the validation of a model constructed in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
147
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 269 publications
(168 citation statements)
references
References 21 publications
1
147
0
Order By: Relevance
“…However, it is reported that the generated wind field by the Fluent code decays rapidly in the inertial range and is not well approximated as the marine random wind [26]. The power spectral density (PSD) of the fluctuating wind is fitted by NPD (Norwegian Petroleum Directorate) spectrum in the present study [22]:…”
Section: Boundary Conditionsmentioning
confidence: 99%
See 4 more Smart Citations
“…However, it is reported that the generated wind field by the Fluent code decays rapidly in the inertial range and is not well approximated as the marine random wind [26]. The power spectral density (PSD) of the fluctuating wind is fitted by NPD (Norwegian Petroleum Directorate) spectrum in the present study [22]:…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…Using the Figure 8: (a) Boundary layer profile at 1st time step at the inlet obtained to simulate the NPD profile [22]. (b) Turbulence intensity measurements at 1st time step at the inlet for NPD profile [22]. (c) Boundary layer profile at 100th time step at 100 m in front of the CFD numerical model obtained to simulate the NPD profile [22].…”
Section: Cfd Wind Tunnel Predictions the Present Work Inmentioning
confidence: 99%
See 3 more Smart Citations